2017
DOI: 10.1016/j.drugalcdep.2017.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of intravenous cocaine administration on serum concentrations of ghrelin, amylin, glucagon-like peptide-1, insulin, leptin and peptide YY and relationships with cardiorespiratory and subjective responses

Abstract: Background Food intake and use of drugs of abuse like cocaine share common central and peripheral physiological pathways. Appetitive hormones play a major role in regulating food intake; however, little is known about the effects of acute cocaine administration on the blood concentrations of these hormones in cocaine users. Methods We evaluated serum concentrations of six appetitive hormones: ghrelin (total and acyl-ghrelin), amylin, glucagon-like peptide-1 (GLP-1), insulin, leptin and peptide YY (PYY), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…Similarly, sCT attenuates the cocaine-induced locomotor stimulation and dopamine release in Nac shell ( Kalafateli et al, 2021 ), and decreases the amphetamine-induced locomotor simulation ( Twery et al, 1986 ; Clementi et al, 1996 ). In humans, cocaine reduces amylin in plasma ( Bouhlal et al, 2017 ; Angarita et al, 2021 ). Additionally to reward induced by addictive drugs, the amylinergic pathway regulates natural rewards like sexual behaviours ( Clementi et al, 1999 ) and hedonic feeding ( Mietlicki-Baase et al, 2013 ; Baisley and Baldo, 2014 ; Mietlicki-Baase et al, 2015 ; Mietlicki-Baase et al, 2017 ; Reiner et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sCT attenuates the cocaine-induced locomotor stimulation and dopamine release in Nac shell ( Kalafateli et al, 2021 ), and decreases the amphetamine-induced locomotor simulation ( Twery et al, 1986 ; Clementi et al, 1996 ). In humans, cocaine reduces amylin in plasma ( Bouhlal et al, 2017 ; Angarita et al, 2021 ). Additionally to reward induced by addictive drugs, the amylinergic pathway regulates natural rewards like sexual behaviours ( Clementi et al, 1999 ) and hedonic feeding ( Mietlicki-Baase et al, 2013 ; Baisley and Baldo, 2014 ; Mietlicki-Baase et al, 2015 ; Mietlicki-Baase et al, 2017 ; Reiner et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, treatment with sCT has been reported to block amphetamine-induced locomotor stimulation in rats [40]. Moreover, a recent study showed a trend of decreased amylin levels after cocaine intravenous injection in cocaine-experienced users [41].…”
Section: Discussionmentioning
confidence: 99%
“…The antagonistic relationship between GLP-1 and cocaine is well supported by preclinical work, as shown above. However, a study finding reduced serum GLP-1 levels in human participants following intravenous cocaine administration shows that this relationship may be bidirectional (Bouhlal et al, 2017).…”
Section: Psychostimulantsmentioning
confidence: 99%